2006
DOI: 10.1051/vetres:2006013
|View full text |Cite
|
Sign up to set email alerts
|

The postnatal development of the mucosal immune system and mucosal tolerance in domestic animals

Abstract: -The mucosal immune system is exposed to a range of antigens associated with pathogens, to which it must mount active immune responses. However, it is also exposed to a large number of harmless antigens associated with food and with commensal microbial flora, to which expression of active, inflammatory immune responses to these antigens is undesirable. The mucosal immune system must contain machinery capable of evaluating the antigens to which it is exposed and mounting appropriate effector or regulatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 57 publications
(61 reference statements)
2
21
0
2
Order By: Relevance
“…Several studies, including humans, swine and mice, demonstrated that small quantities of food proteins absorb intact across the intestinal epithelium in adults and neonates (Bailey et al, 1994;Telemo et al, 1991). Recent studies of the phenomenon of oral tolerance suggest that it is variable and age-dependent (Bailey & Haverson, 2006) as well as the present of commensal microbial flora in the intestine.…”
Section: Intestinal Mucosal Immune System (Imis): Paradoxycal Role Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including humans, swine and mice, demonstrated that small quantities of food proteins absorb intact across the intestinal epithelium in adults and neonates (Bailey et al, 1994;Telemo et al, 1991). Recent studies of the phenomenon of oral tolerance suggest that it is variable and age-dependent (Bailey & Haverson, 2006) as well as the present of commensal microbial flora in the intestine.…”
Section: Intestinal Mucosal Immune System (Imis): Paradoxycal Role Tomentioning
confidence: 99%
“…Theirs' APCs expressing MHC II protein class. Immature dendritic cells are present in large numbers within the villi and co-localise with T-cells expressing the CD4 coreceptor in the pig, but expressing the low affinity Fc RIII (Bailey & Haverson, 2006). The point is that diffuse mucosal tissue has the first role in immune regulation, rather than active defensive responses.…”
Section: The Diffuse Lymphoid Tissuesmentioning
confidence: 99%
“…However, although some mechanisms of the host, such as the gastrointestinal mucosal barrier, are suggested to play an important role in host-pathogen interaction [1], it is still unclear how interaction between immunity and Salmonella at the site affect the induction of these inflammatory reactions. Furthermore, as the structure and components of the mucosal immune system in the gut of young animals differ from those of adult animals [5,22], host-pathogen interaction and subsequent clinical signs may vary greatly depending on the level of maturity of this immune system. The mechanisms involved in immunity in the most susceptible age group of calves may be very complex.…”
Section: Groupmentioning
confidence: 99%
“…La presencia de IgG frente a antígenos de la dieta también se ha estudiado en animales de producción, principalmente en lechones y terneros frente a la soja (Bailey y Haverson, 2006). Los problemas por el uso de soja se asocian a la presencia de factores antinutricionales y proteínas antigénicas como glicinina y β-conglicinina (Huisman y Jansman, 1991).…”
Section: Las Igg Como Marcadores De La Reacción Inmunitaria Frente a unclassified
“…La antigenicidad de la harina de soja ha sido muy estudiada en lechones y terneros (Bailey y Haverson, 2006) y también se sabe que la utilización de guisante en piensos de iniciación de lechones provoca un aumento de IgG específicas en mucha mayor medida que la caseína (Salgado et al, 2002a). Por el contrario, no se ha encontrado información sobre la antigenicidad de la harina de girasol, probablemente por su escasa utilización en piensos para lechones y terneros (De Blas et al, 2010).…”
Section: Evolución De Las Igg Frente a Antígenos Dietarios En El Suerunclassified